2020
DOI: 10.1002/oby.22771
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Glucose Concentrations in Early Pregnancy and Cardiometabolic Risk Factors in Childhood

Abstract: Objective: This study aimed to examine the associations of maternal early-pregnancy glucose and insulin concentrations with offspring cardiometabolic risk factors and fat distribution. Methods: In a population-based prospective cohort study among 3,737 mothers and their children, random maternal glucose and insulin concentrations were measured at a median gestational age of 13.2 (95% range 10.5-17.1) weeks. Childhood fat, blood pressure, and blood concentrations of lipids, glucose, and insulin at the age of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
6
16
0
Order By: Relevance
“…Maternal glucose concentrations were not associated with DNA methylation levels at the two identified CpGs in peripheral blood of 10-year-old children (p values > 0.1) (Additional file 7: Table S8). In exploratory analyses, the two identified CpGs were not associated with birth weight or childhood glucose concentrations, which both were previously found to be associated with maternal early-pregnancy glucose concentrations in our data (p values > 0.1) [9,13].…”
Section: Associations Of Maternal Early-pregnancy Glucose and Insulinsupporting
confidence: 45%
See 3 more Smart Citations
“…Maternal glucose concentrations were not associated with DNA methylation levels at the two identified CpGs in peripheral blood of 10-year-old children (p values > 0.1) (Additional file 7: Table S8). In exploratory analyses, the two identified CpGs were not associated with birth weight or childhood glucose concentrations, which both were previously found to be associated with maternal early-pregnancy glucose concentrations in our data (p values > 0.1) [9,13].…”
Section: Associations Of Maternal Early-pregnancy Glucose and Insulinsupporting
confidence: 45%
“…It has been suggested that women who develop gestational diabetes or hyperglycemia later in pregnancy already have suboptimal glucose metabolism before or in early pregnancy [43,44]. Maternal glycemic measures in early pregnancy have been described to be associated with altered fetal growth and glucose metabolism in childhood, but not with child adiposity, lipid levels, and blood pressure after adjustment for maternal pre-pregnancy BMI [9,12,13]. Thus, early pregnancy may already be a critical period for the effects of maternal glucose concentrations on offspring birth outcomes and glycemic health in childhood.…”
Section: Interpretation Of Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…118 This is also reflected in a recent human study in the Generation R birth cohort that reported high maternal insulin concentration in early gestation is associated with increased systolic blood pressure in offspring, although these associations attenuated to non-significance after adjustment for maternal BMI, suggesting that hypertension is programmed by other factors related to maternal weight than hyperinsulinaemia. 119 Future studies in animal models may help to delineate the contribution of maternal circulating factors independent of each other and of maternal BMI.…”
Section: Interventions During Ob E S E/g Dm Preg Nan Cie Smentioning
confidence: 99%